Blastocystis and Clostridioides difficile: Evidence for a Synergistic Role in Colonization Among IBD Patients with Emphasis on Ulcerative Colitis - Azimirad, Masoumeh; Gol, Sara Mohammad Ali; Javanmard, Ehsan; Mirjalali, Hamed; Yadegar, Abbas; Aghdaei, Hamid Asadzadeh; Shahrokh, Shabnam; Balaii, Hedieh; Sadeghi, Amir; Zali, Mohammad Reza (Turkish Journal of Gastroenterology, 2021)
Background: Regarding the controversial role of Blastocystis in inflammatory bowel diseases (IBD) patients, it seems that this protozoanmay lead to an overgrowth of some non-beneficial bacteria. The current study aimed to investigate the co-existence of Blastocystis andClostridioides difficile in IBD patients.Methods: Stool samples of 102 IBD patients were collected and cultivated for C. difficile and Blastocystis. DNA extraction was performedon positive samples and C. difficile and Blastocystis were toxinotyped and subtyped, respectively. Fisher’s exact test and logistic regressionwere employed to calculate the correlation between the existence of Blastocystis and its subtypes (ST) with C. difficile and its typeof toxins. Also, the co-existence of Blastocystis and C. difficile with the frequency of defecations was evaluated.Results: Blastocystis and C. difficile were observed in 17 (16.7%) and 26 (25.5%) of stool samples, respectively. From 26 C. difficilepositiveisolates, 24 (92.3%) and 2 (7.7%) were tcdA+/B+ and tcdA+/B-, respectively. Also, 10 (58.8%) and 7 (41.2%) were BlastocystisST1 and ST3, respectively. Statistically significant correlations between co-existence of Blastocystis and C. difficile and co-existenceof these microorganisms and frequency of defecation (P < .035) were seen. There was no statistically significant correlation betweensubtypes of Blastocystis and colonization of C. difficile or its toxinotypes.Conclusion: The co-existence of Blastocystis and C. difficile in IBD patients was observed in the current study. Moreover, it can be proposedthat these microorganisms may have synergistic effects on their colonization in the gastrointestinal tract.